2016
DOI: 10.1021/acsami.6b11984
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Carbon Nanotube/Polyaniline Porous Network for Multifunctional Applications

Abstract: Three-dimensional carbon nanotube (CNT) networks with high porosity and electrical conductivity have many potential applications in energy and environmental areas, but the network structure is not very stable due to weak inter-CNT interactions. Here, we coat a thin polyaniline (PANI) layer on as-synthesized CNT sponge to obtain a mechanically and electrically stable network, and enable multifunctional applications. The resulting CNT/PANI network serves as stable strain sensors, highly compressible supercapacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Meanwhile, the presence of N atoms in graphene electrode significantly provides pseudocapacitance for the full capacitance. [45][46][47] Therefore, the supercapacitive performance of the N-doped LIG was highly improved. Furthermore, the MSCs can exhibit an area special capacitance up to about 790 µF cm −2 at the discharge current of 50 µA cm −2 , which is higher than the value of supercapacitors on PDMS including LIG and reduced graphene oxide (Table S1, Supporting Information).…”
Section: Doi: 101002/smll201702249mentioning
confidence: 99%
“…Meanwhile, the presence of N atoms in graphene electrode significantly provides pseudocapacitance for the full capacitance. [45][46][47] Therefore, the supercapacitive performance of the N-doped LIG was highly improved. Furthermore, the MSCs can exhibit an area special capacitance up to about 790 µF cm −2 at the discharge current of 50 µA cm −2 , which is higher than the value of supercapacitors on PDMS including LIG and reduced graphene oxide (Table S1, Supporting Information).…”
Section: Doi: 101002/smll201702249mentioning
confidence: 99%
“…The pristine flexibility of the CNF paper was maintained and simultaneously the electronic conductivity was improved (2.43, 0.95, and 0.6 S cm −1 for CNF–PANI, CNF paper, and PANI, respectively). Zhao et al . found that a thin PANI layer was coated onto a CNT sponge through electrodeposition for compressible SCP electrodes; the obtained mechanically and electrically stable CNT–PANI core–shell sponge had an increased conductivity of 186 S m −1 compared to 81 S m −1 for the CNT sponge.…”
Section: Applications Of Panimentioning
confidence: 99%
“…For instance, Yan et al [98] preparedafreestanding CNF-PANI composite by depositing PANI NPs onto the surface of each CNF.T he pristine flexibility of the CNF paper was maintained ands imultaneously the electronic conductivity was improved (2.43, 0.95, and 0.6 Scm À1 for CNF-PANI, CNF paper,a nd PANI, respectively). Zhao et al [99] found that at hin PANI layer was coated onto a CNT sponge through electrodeposition for compressible SCP electrodes;t he obtained mechanically and electrically stable CNT-PANI core-shell sponge had an increasedc onductivity of 186 Sm À1 compared to 81 Sm À1 for the CNT sponge. The increasede lectronic conductivity was attributed to the continuous and uniform PANI layer.T his layer not only created the cross-junction between CNT networks that reduced contact resistanceb ut provided conductive pathways in the composite.…”
Section: Pani/carbonmentioning
confidence: 99%
“…In addition to CNT film and arrays, other CNT nanostructures have also been developed for use in flexible supercapacitors, such as CNT networks [72], CNT sponges [73][74][75], and CNT yarn [76][77][78]. These CNT structures are often used as conductive skeletons/substrates, and provide a large surface area for the deposition of secondary active materials by following the so-called core-sheath/shell model.…”
Section: Other Cnt Nanostructuresmentioning
confidence: 99%